Pilot study on 11C-CFT dynamic imaging using total-body PET/CT: biodistribution and radiation dosimetry in Parkinson's disease - Xin, Mei; Li, Lianghua; Wang, Cheng; Shao, Hongda; Liu, Jianjun; Zhang, Chenpeng (Frontiers in Neurology, 2023)
Objective: Total-body PET/CT equipment, uEXPLORER, is a newly developed imaging technology with super-high resolution, sensitivity, and signal-to-noise ratio, providing unique application advantages in pharmacokinetic evaluation of positron tracers. While 11C-CFT PET/CT has been widely utilized in the early diagnosis of Parkinson’s disease (PD), it is limited by the short half-life of the radionuclide and incomplete understanding of human biological distribution. The objective of this study is to utilize total-body PET/CT dynamic scan on 11C-CFT imaging to describe real-time internal biodistribution in PD patients and obtain precise radiation dosimetry. Methods: Six male subjects with suspected PD underwent dynamic 11C-CFT total-body PET/CT. After a bedside bolus injection of 373.3 ± 71.56 MBq of 11C-CFT, PET acquisition with a maximum axial field of view (AFOV) of 194 cm was carried out synchronously for 75 minutes. Time-activity curves (TACs) were generated by delineating volumes of interest (VOIs) of sourced organs using PMOD software. Tracer kinetics and cumulative organ activities were calculated, and absorbed doses were computed and estimated using the OLINDA/EXM software. Results: In the systemic TAC analysis of 11C-CFT, several unique types of distribution patterns were obtained among the main organs, including a “Fast-in Fast-out” pattern in the kidney, lung, spleen, and thyroid, a “Fast-in Slow-out” curve in the heart wall, a “Slow-in Slow-out” mode in the liver, a “Low-level extending” pattern in the whole brain and muscle, and a “Slow-in to plateau” trend in the striatum and bone. The effective dose of 11C-CFT was calculated as 2.83E-03 mSv/MBq, which is only one-third of the literature value measured by the conventional method. Moreover, this dose is also much lower than any other comparable DAT radioligands used in PET imaging. Conclusions: This study is a pioneer application of total-body PET/CT on 11C-CFT dynamic imaging. Our results confirm that 11C-CFT has a favorable total body biodistribution, extremely low internal radiation dose, and high imaging quality, making it suitable for reasonable PD diagnosis and patients requiring multiple follow-up examinations.